2018
DOI: 10.1002/bbb.1864
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae cultivation and metabolites production: a comprehensive review

Abstract: Microalgae have important potential in the bio‐based industry. However, their light‐utilization mechanisms are still not fully understood. Together with knowledge of their metabolic pathways and their responses in carbon partitioning to different primary metabolites (carbohydrates, lipids and proteins), this information is essential if their potential and profitability are to be better exploited. The first part of this review describes the techniques used for microalgae cultivation and the growth factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 180 publications
1
44
0
5
Order By: Relevance
“…Further, it has been suggested that in microalgae species with moderate amounts of lipids could be possible to improve these amounts by modifying the culture conditions and nutrient availability. In that sense, it is well documented that under deficient nutrient conditions, neutral lipids synthesis is favored and can be used as an alternative source of biofuels; therefore, it is necessary to find the most suitable species and define the culture conditions that could help to achieve this purpose (Vuppaladadiyam et al, 2018;Zulu et al, 2018).…”
mentioning
confidence: 99%
“…Further, it has been suggested that in microalgae species with moderate amounts of lipids could be possible to improve these amounts by modifying the culture conditions and nutrient availability. In that sense, it is well documented that under deficient nutrient conditions, neutral lipids synthesis is favored and can be used as an alternative source of biofuels; therefore, it is necessary to find the most suitable species and define the culture conditions that could help to achieve this purpose (Vuppaladadiyam et al, 2018;Zulu et al, 2018).…”
mentioning
confidence: 99%
“…Table 1 shows different marine microalgae species that have the potential to produce multiple compounds. Marine microalgal carbohydrates are mainly present as cellulose in the cell wall and starch in the plastid [32]. Monosaccharides are the basic components of carbohydrates in microalgae, which consist of glucose, galactose, mannose, rhamnose, arabinose, xylose, ribose, and fucose [33].…”
Section: Metabolic Network Of Marine Microalgal Metabolitesmentioning
confidence: 99%
“…Microalgae are cultivated either in open pond systems or in closed reactor systems. A photobioreactor is used in microalgae cultivation by implementing bubble columns, airlift, tubular, flat-plate and stirred tank reactors [40]. A more comprehensive description of microalgae cultivation methods can be found elsewhere [41].…”
Section: Microalgae Cultivation Harvesting and Dewateringmentioning
confidence: 99%